In-depth immunophenotyping data of IL-6R on the human peripheral regulatory T cell (Treg) compartment - Ferreira, R; Rainbow, D; Garcia, A; Pekalski, M; Porter, L; Oliveira, J; Waldron-Lynch, F; Wicker, L; Todd, J (Elsevier, 2017)
We provide in this paper a detailed characterization of the human peripheral CD4+ CD127lowCD25+ regulatory T cell (Treg) compartment, with a particular emphasis in defining the population expressing higher levels of the IL-6 receptor (IL-6R). We provide a description of the phenotype of this population by assessing both the surface expression by flow cytometry as well as their transcriptional profile and functional features. In addition, we also present functional data describing the responsiveness of these subsets to IL-6 signalling in vitro and to IL-2 in vivo. The data presented in this paper support the research article “Human IL-6RhiTIGIT− CD4+CD127lowCD25+ T cells display potent in vitro suppressive capacity and a distinct Th17 profile